Arthur Johnston and the fostering of Scottish letters - Farquhar, AJK (2014)
Traditionally, Arthur Johnston has been judged proxime accessit to George Buchanan in the world of Scottish neo-Latin poetry, and particularly in the versification of the Book of Psalms. The thesis offers a counterpoint to that theme. More of his poetry came under scrutiny at the close of the nineteenth century, when an edition of his Parerga and Epigrammata of 1632, turned scholarly attention to his secular poems. This study examines the poems written between 1599 and 1622 during Johnston’s peregrenatio academica in Europe – poems which depict him at the moment of his emergence onto the public stage, and which offer insights into his life, and the worlds he occupied, during those years. Part one of the thesis will examine his early years and his move into the academic world in Aberdeen and at Heidelberg University. Part two will consider the years he passed as a teacher of philosophy at the Huguenot Academy in Sedan, the independent principality on the northern border of France. It will look, too, at the evidence of his year spent in Padua, where he studied to become a physician. Part three will focus on the years 1619-22 when his longest secular poems were composed. He wrote and published with an eye to achieving a post in the medical circle around James VI and I. The thesis concludes by considering the retreat he made from Europe and London to his home in Aberdeen, and looks briefly at one of the small poems he wrote in 1623-24. Throughout, themes emerge of Johnston’s irenic preferences, and his response to the disturbance to intellectual life brought about by Calvinist division, and by the crisis heralded by the Bohemian Revolt.